Authoritarianism in the 21st Century: A Proposal for Measuring Authoritarian Attitudes in Neoliberalism - Esmeralda Nicieza-Cueto; María de la Villa Moral-Jiménez (Social Sciences)
The continuous crises of the neoliberal system have led to an authoritarian turn, with authoritarianism acquiring a different dimension since the studies of Altemeyer in 1981. The aim of the present study is to elaborate a scale to measure authoritarianism adapted to the contemporary era, the Neoliberal Authoritarianism Scale, and to test its validity and reliability. 232 people between the ages of 18 and 81 (X = 38.34; SD = 13.141) residing in Spain participated, consisting of 51.7% women and 38.8% men. Confirmatory factor analysis revealed a good fit of the four-factor model (χ2/df = 1.92; CFI = 0.993; TLI = 0.992; IFI = 0.993; GFI = 0.986; RMSEA = 0.041; SRMR = 0.063). The scale also showed an adequate internal consistency, with a global McDonald’s Omega of 0.893. Nevertheless, the Conventionalism factor needs to be improved (ω = 0.621). This scale is a first preliminary approach to measuring neoliberal authoritarianism, which may help to better understand its scope and impact on people’s lives.